Connection Knowledge Nurse with Attitude and Implementation Target Safety Patient (STIKES Telogorejo Semarang, 2023)
Patient safety is an important part of health care. Patient safety is important in preventing and reducing risks, errors and injuries that can occur during service. The role of nurses in improving patient safety in hospitals must be able to actively participate in realizing it properly. Nurses' knowledge of patient safety greatly influences the performance of nurses in implementing and implementing patient safety actions in hospitals. This study uses a descriptive correlation research design type of quantitative method with a cross-sectional research approach. The results of this study are expected to be a reference for improving the quality of nurses' professionalism in implementing patient safety. Based on data analysis using the Sparman Rank statistical test between nurses' knowledge and patient safety attitudes, the results of the p value were 0.033 (<0.05) which means Ha is accepted, where there is a significant relationship between nurses' knowledge and patient safety attitudes, with a correlation coefficient value of 0.428, namely the level of relationship strength is sufficient, with a positive correlation direction. The results of this study are expected to be a reference for improving the quality of nurses' professionalism in implementing patient safety.